The Correlation Between Behavioral and Psychological Factors with Booster Immunization Adherence for Children Aged - Ayun Sriatmi; Martini Martini; Sutopo Patriajati; Budiyono Budiyono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: Immunization status is considered complete when children receive all antigens types as recommended, including booster immunization, ensuring optimal protection. The high level of non-adherence is the main obstacle to immunization programs, further added by the fact that the number of children who receive partial or no immunization remains high. This study aims to analyze the correlation between behavioral and psychological factors with booster immunization adherence in children aged <24 months.Method: A quantitative study with a cross-sectional approach. The population consists of parents with children aged 18-23 months, totaling a sample of 522 children. The data were collected through interviews using structured questionnaires, and observations using MCH-Book to measure booster immunization adherence. The collected data was analyzed through univariate, bivariate, and multivariate approaches with multiple logistic regression tests to identify the dominant variables.Results: Only 25.9% of children received two types of recommended booster vaccines (DPT/HB/HiB-4 and MR-2). Partially, behavioral factors that correlate with booster immunization adherence are knowledge, attitudes, and perceptions about multiple injections, while psychological factors that correlate are motivation and basic immunization status. Experience with previous basic immunization status is the most dominant factor influencing booster immunization adherence. The fear of disease infection and trust in healthcare providers are the keys to a successful immunization. Need to increase motivation through strengthening literacy and improving access to and health service system to reduce hesitation about, distrust, and refusal of immunization, while also providing a positive immunization experience.